Evidence-Based Practice in Teacher Education: The Mediating Role of Self-Efficacy Beliefs and Practical Knowledge - Georgiou, Despoina; Mok, Sog Yee; Fischer, Frank; Vermunt, Jan D.; Seidel, Tina (Frontiers in Education, 2020)
European educational reforms call for the implementation of evidence-based teaching (EBT) in universities. Based on the evidence-based research paradigm in medical education, this study investigates the relationship between teacher educators’ research experience, practical knowledge, self-efficacy beliefs, and frequency of EBT implementation. We report on survey data from N = 243 teacher educators from Germany, Austria, Switzerland, and the United Kingdom. A set of mediation analyses were run to identify the mediating role of self-efficacy beliefs and practical knowledge in the interplay among teacher educators' research experience and frequency of research evidence implementation. The results indicate that self-efficacy beliefs are a strong predictor of how frequently teacher educators implement EBT. Implications about the role of self-efficacy beliefs in teacher educators’ professional learning and development along with future steps that are necessary to increase the implementation of EBT practices in teacher education will be discussed.